2013
DOI: 10.1002/ase.1372
|View full text |Cite
|
Sign up to set email alerts
|

Medical students' understanding of the concept of a soul

Abstract: The concept of a soul has been discussed throughout religious, philosophical, and scientific circles, yet no definitive description exists. Recent interviews with medical students during the production of a documentary film identified that many believed in the concept of a soul. This study explores students' understanding of the concept of a soul. The 2011 cohort of second-year medical students at the University of Otago in Dunedin, New Zealand were invited to participate in an online survey with a free text r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…While many students held a dualistic view of the soul, there was a wide range of interpretations of the soul (Martyn et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many students held a dualistic view of the soul, there was a wide range of interpretations of the soul (Martyn et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative component explored students' definition of the soul. Students often described the soul as the 'life force' or the 'spiritual essence of a person' (Martyn et al 2013). While many students held a dualistic view of the soul, there was a wide range of interpretations of the soul (Martyn et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These findings confirmed those of Bohl et al (), demonstrating that students want more information and less anonymity with respect to their body donors. This high degree of interest could possibly be explained by data that have been presented by Martyn et al (). These authors demonstrated that students in the dissection course spend more time reflecting on the concept of the soul (Martyn et al, ), and that this reflection on (im)mortality represents an opportunity for further professional and personal development (Martyn et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This high degree of interest could possibly be explained by data that have been presented by Martyn et al (2013). These authors demonstrated that students in the dissection course spend more time reflecting on the concept of the soul (Martyn et al, 2012), and that this reflection on (im)mortality represents an opportunity for further professional and personal development (Martyn et al, 2013). The findings of Bohl et al (2013) are based on a considerably lower response rate (33%).…”
Section: Students' Opinionsmentioning
confidence: 99%
“…During the course of dissection, these students have developed coping strategies to ameliorate these behavioural responses. The second theme of responses was 'human referents' where students consider the cadaver like a "living person" having a previous life story, family, human-like appearance, and special organs like the brain and eyes [29]. In our study, we further classified the responses as cognitive, affective and moral.…”
Section: Discussionmentioning
confidence: 99%